2001
DOI: 10.1034/j.1600-0676.2001.021003207.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of an intravenous monoclonal anti‐HBs in chronic hepatitis B patients

Abstract: We conclude that Mab was not effective in achieving primary efficacy as assessed by neutralization of circulating HBsAg. Whether a combination of Mab with an antiviral agent that reduces the HBsAg load--and therefore minimizes the risk of adverse events--may result in clinical efficacy should be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 16 publications
1
10
1
Order By: Relevance
“…The near identity of clones of HBV bNAbs in unrelated elite individuals is akin to reports for elite responders to HIV-1 (Scheid et al, 2011; West et al, 2012), influenza (Laursen and Wilson, 2013; Pappas et al, 2014; Wrammert et al, 2011), Zika (Robbiani et al, 2017), and malaria (Tan et al, 2018). However, none of the elite anti-HBs bNAbs shares both IgH and IgL with previously reported HBV neutralizing antibodies, the best of which have been tested in the clinic but are less potent than some of the bNAbs reported here (libivirumab IC 50 : 35 ng/ml, tuvirumab IC 50 : ~100 ng/ml) (Galun et al, 2002; Heijtink et al, 2001; van Nunen et al, 2001).…”
Section: Discussioncontrasting
confidence: 53%
“…The near identity of clones of HBV bNAbs in unrelated elite individuals is akin to reports for elite responders to HIV-1 (Scheid et al, 2011; West et al, 2012), influenza (Laursen and Wilson, 2013; Pappas et al, 2014; Wrammert et al, 2011), Zika (Robbiani et al, 2017), and malaria (Tan et al, 2018). However, none of the elite anti-HBs bNAbs shares both IgH and IgL with previously reported HBV neutralizing antibodies, the best of which have been tested in the clinic but are less potent than some of the bNAbs reported here (libivirumab IC 50 : 35 ng/ml, tuvirumab IC 50 : ~100 ng/ml) (Galun et al, 2002; Heijtink et al, 2001; van Nunen et al, 2001).…”
Section: Discussioncontrasting
confidence: 53%
“…The success of HBIG in these conditions raises the possibility of antibody-mediated immunotherapy against chronic HBV infection (25). Indeed, three pioneering studies tested the efficacy of anti-HBs monoclonal antibodies or HBIG in CHB patients, alone or in combination with alpha-interferon (4446). All these studies demonstrated the temporary reduction of HBsAg and HBV DNA after a high dose of anti-HBs antibody treatment, though the long-term clearance of HBsAg was not observed.…”
Section: The Efficacy Of Antibody-medicated Immunotherapy or Triggerimentioning
confidence: 99%
“…The efficacy of specific antibody mediated reduction of HBsAg has been described in a previous section of this review. It is shown that using HBIG or monoclonal antibodies against HBsAg can efficiently decrease the serum level of HBsAg in CHB patients (4447). In addition, high affinity human anti-HBs and anti-Pre-S1-monoclonal antibodies have been developed recently, and these antibodies have shown an excellent ability to efficiently clear circulating HBsAg in different mouse models (103106).…”
Section: How To Optimize the Therapeutic Efficacy Of Strategies Targementioning
confidence: 99%
“…Notably, a murine anti-HBs mAb was employed to treat hypogammaglobulinemic HBV-infected individuals yielding reduced HBV DNA levels (44). Moreover, a human anti-HBs mAb, alone or in combination with interferon-α, was used in patients with chronic HBV infection, resulting in a substantial decrease in HBsAg titers (45). Interestingly, combination therapy with interferon-α successfully cleared HBsAg.…”
Section: Perspective For a Combined Use Of Humabs And Nucleos(t)ide Amentioning
confidence: 99%